Basic and clinical research on renal cell carcinoma - Staehler, Gerd 1939-2014; Pomer, Sigmund (Springer Berlin Heidelberg, 1992)
Advanced Renal Cell Carcinoma (RCC) cannot be cured by surgery alone. Its resillience to irradiation and chemotherapy demands a new approach to the management of this disease. This book provides an overview of the scientific and clinical developments of RCC, and clarifies the fields ofimmunotherapy and immunobiology. The book contains a compilation of approaches that will enhance the effectiveness of the management of advancedRCC, even in the absence of definitive pre-clinical data. These require additional study and will stimulate the reassessment of preliminary results.Furthermore, preliminary results of already implemented clinical trials withbiological modifiers are presented. Of special interest are the current achievements in the field of immunotherapy using topically and subcutaneously low dosage combinations of cytokines. This concise volume will benefit those seeking a thorough review of the research and the clinical aspects of RCC simultaneously
Keywords: Hypernephrom